2017
DOI: 10.1590/01047760201723012247
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Vertical Distribution of Litter and Belowground Carbon in a Brazilian Cerrado Vegetation

Abstract: Forest ecosystems contribute significantly to store greenhouse gases. This paper aimed to investigate the spatial and vertical distribution of litter, roots, and soil carbon. We obtained biomass and carbon of compartments (litter, roots, and soil) in a vegetation from Cerrado biome, state of Minas Gerais, Brazil. The materials were collected in 7 0.5 m² sub-plots randomly allocated in the vegetation. Root and soil samples were taken from five soil layers across the 0-100 cm depth. Roots were classified into th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 30 publications
1
11
1
9
Order By: Relevance
“…Torres et al (2013) observed an average of 52% of C content in the litter in a Semi-Deciduous Seasonal Forest in Minas Gerais. On the other hand, Higuchi & Carvalho (1994), in a Tropical Forest in the Amazon Region, and Morais et al (2017), in the Cerrado vegetation of the state of Minas Gerais, found mean C contents in the litter of 39% and 44%, respectively.…”
Section: Organic Carbon In Littermentioning
confidence: 95%
“…Torres et al (2013) observed an average of 52% of C content in the litter in a Semi-Deciduous Seasonal Forest in Minas Gerais. On the other hand, Higuchi & Carvalho (1994), in a Tropical Forest in the Amazon Region, and Morais et al (2017), in the Cerrado vegetation of the state of Minas Gerais, found mean C contents in the litter of 39% and 44%, respectively.…”
Section: Organic Carbon In Littermentioning
confidence: 95%
“…Some research points to the ability of the Cerrado biome as a carbon sink (Morais et al, 2017;Pellegrini, Socolar, Elsen, & Giam, 2016). Interestingly, fires in the Cerrado biome may be beneficial to the biome, according to Pilon, Hoffmann, Abreu, and Durigan (2018) fire triggers important ecological processes in Cerrado grasslands, such as seed production and the genetic diversity of many species.…”
Section: Effects Of the Fires On The Gross Primary Productivity (Gpp)mentioning
confidence: 99%
“…Contudo, o estoque de carbono pode ser melhor estimado e a variação visualizada com a aplicação de técnicas espaciais, como a geoestatística (MORAIS et al, 2017;SCOLFORO et al, 2015SCOLFORO et al, , 2016 O projeto está dividido em três fases:…”
Section: José Márcio De Mellounclassified